Exploring User Needs for a Household Compost Bag Kit Made from Used Banners Using a Human-Centered Design Approach - Baridah Mutmainah; Flavia Alice Mameli; Khansa Vidyaprabha (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Household organic waste remains the largest contributor to urban waste generation in Indonesia. Although it has the potential to be processed into compost, composting at the household level is not yet widely practiced. One of the reasons for this is the lack of practical, user-friendly facilities that meet users’ needs. On the other hand, waste from used banners from various promotional activities continues to increase every year, and the majority of this has not yet been utilized optimally. In fact, this material is strong, water-resistant and has the potential to be recycled into functional products of practical value. This study aims to develop a design for a household compost bag kit made from used banners using a Human-Centered Design (HCD) approach. The selection of used banners as the primary material is based on their suitability for the product’s functional requirements, while also serving as an application of the principle of upcycling. The research was conducted using qualitative methods through the stages of inspiration, ideation, and implementation. Data were collected through observation, in-depth interviews, and prototype evaluations involving prospective household users. The results of the study indicate that ease of use is the primary consideration for users when selecting a household composting device. Furthermore, the product’s ability to control odors, ease of transport, and the availability of clear composting guidelines were also identified as important requirements expressed by respondents